2015
DOI: 10.1089/ars.2015.6320
|View full text |Cite
|
Sign up to set email alerts
|

Can l-Cysteine and Vitamin D Rescue Vitamin D and Vitamin D Binding Protein Levels in Blood Plasma of African American Type 2 Diabetic Patients?

Abstract: Aims: Vitamin D (VD) deficiency has become a worldwide epidemic, particularly affecting African Americans (AA). VD deficiency has been implicated in the excessive rate of complications associated with diabetes in AA. Blood levels of VD binding protein (VDBP) and glutathione (GSH) are lower in AA compared with those in Caucasians. This study tested the hypothesis that lower GSH levels are linked to VDBP and VD deficiency in AA-type 2 diabetic (AA-T2D) patients. Blood was analyzed from T2D and nondiabetic subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…In chemistry, NAC is derived from L-cysteine, whose amino-group is acetylated. It was reported that L-cysteine, as well as its metabolite H 2 S, is decreased in African Americans with Type 2 DM [11, 12]. Another report suggested that NAC can react with MGO to produce N-α-acetyl-S-(1-hydroxy-2-oxo-prop-1-yl)cysteine [13].…”
Section: Introductionmentioning
confidence: 99%
“…In chemistry, NAC is derived from L-cysteine, whose amino-group is acetylated. It was reported that L-cysteine, as well as its metabolite H 2 S, is decreased in African Americans with Type 2 DM [11, 12]. Another report suggested that NAC can react with MGO to produce N-α-acetyl-S-(1-hydroxy-2-oxo-prop-1-yl)cysteine [13].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, it has been pointed out that positive link between plasma levels of VDBP and 25(OH)D and those of GSH; specifically, lower plasma levels of VDBP and 25(OH)D correlated with lower GSH level, and increases in GSH level upregulated 25(OH)D and VDBP status in Zucker diabetic fatty rats . Supplementation of GSH could raise blood levels of VDBP and vitamin in African‐American patients with type 2 diabetes . Another study also suggested a significant positive correlation between GSH level and blood levels of L‐cysteine (LC) and vitamin D in type 2 diabetic patients .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in the literature report lower blood levels of VDBP, 25(OH) vitamin D, LC, and GSH in diabetes . GSH is a physiological antioxidant, a co‐factor of many enzymes, and plays an important role in a multitude of cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Epidimiological studies demonstrate that higher rates of deficiency of 25‐hydroxy‐vitamin D could be linked to the prevalence of several chronic diseases, including diabetes . Previous studies have reported an association between lower blood levels of 25(OH) vitamin D, VDBP, and GSH in diabetic patients, and in African‐American subjects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation